Przenikanie języków i kultur w średniopolskiej antroponimii Krakowa (XVI–XVIII wiek) - Rudnicka-Fira, Elżbieta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
This article explores the influence of external (foreign) contacts, various languages and cultures on the anthroponymy (surnames) of Kraków’s inhabitants during the Early Modern Polish period. Kraków’s ties with other countries and nations are reflected in certain surname forms, which, as they assimilated into Polish, underwent various adaptation processes – adjusting to native pronunciation and orthography, and conforming to Polish inflectional and word-formation norms. This led to the emergence of distinctive linguistic derivatives (hybrids) – familial forms created using systematic Polish surname-forming suffixes. It is of particular interest how extralinguistic factors – such as social evolution, urban development, foreign interactions, customs, behavioral patterns, and family traditions – shaped the linguistic form of surnames, their lexical origins, and the application of different surname types for identifying various social categories. As research into this fascinating material has shown, the intermingling of different languages and cultures, evident in the anthroponymy of Kraków during the Middle Polish period, occurred in many diverse aspects – not only formal and structural, but also within a broader cultural, sociopolitical and other contexts. Surnames of foreign origin, rooted in the Polish anthroponymic inventory (in various configurations), point to the numerous international connections of Kraków at the time, thus marking an integral part of its history.